2012
DOI: 10.1210/jc.2012-1532
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells in Human Adipose Tissue: Link with Morbid Obesity, Inflammatory Status, and Diabetes

Abstract: Mast cells are cellular actors of WAT inflammation and possibly fibrotic state found in obesity and diabetes. Whether mast cells could be involved in the pathophysiology of diabetes needs additional study as well as the positioning of these cells in driving pathological alterations of WAT in these chronic metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 27 publications
2
116
0
2
Order By: Relevance
“…It has been reported that the serum levels of mast cell-derived tryptase and the number of adipose tissue mast cells are increased in obese patients and high fat diet-fed mice, respectively (42,43). Mast cells in adipose tissue have been proposed to contribute to the pathophysiology of obesity and diabetes and related systemic inflammation (44). MS and some components in particular (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the serum levels of mast cell-derived tryptase and the number of adipose tissue mast cells are increased in obese patients and high fat diet-fed mice, respectively (42,43). Mast cells in adipose tissue have been proposed to contribute to the pathophysiology of obesity and diabetes and related systemic inflammation (44). MS and some components in particular (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mast cells in visceral fat of obese mice [15] and in human subcutaneous abdominal fat [2], suggests their role in the pathogenesis of obesity and insulin resistance and infl ammatory status [2,15]. Similarly ,in an adult prospective study examining the effect of fat distribution on asthma found that abdominal obesity was a risk factor for incident asthma in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are found to be more abundant in subcutaneous abdominal adipose tissue from obese humans than from non-obese humans [2]. Total serum tryptase (ST) could be considered as a measure of mast cell activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Of special importance in fibrosis are mast cells that, besides having an immune function, have recently been identified to play an important role in disease processes. Divoux et al, (2012) reported that mast cells were activated in human adipose tissue and were localised at regions where fibrosis occurs. Mast cells are also implicated in the development of lung fibrosis in that 5-HT is taken up from the serum via the 5-HT transporter (SERT) and carried to the site of injury where it is released.…”
Section: Discussionmentioning
confidence: 99%